Impact of Additives on Poly(acrylonitrile-butadiene-styrene) Membrane Formation Process Using Non-Solvent-Induced Phase Separation - Sulaiman Dhameri; Jason Stallings; Endras Fadhilah; Emily Ingram; Mara Leach; Anastasiia Aronova; Malgorzata Chwatko (Membranes, 2025)
Poly(acrylonitrile-butadiene-styrene) (ABS) is a common polymer used in toys, automobile parts, and membranes. Membranes fabricated with this copolymer commonly employ toxic solvents and have a dense architecture, which may not work in all applications. This work investigates the synthesis of ABS membranes, using green solvents and the influence of additives on the phase inversion process during the non-solvent-induced phase separation. The addition of water-soluble additives, ethanol, and acetone is hypothesized to provide additional control over viscosity and volatility, and, consequently, impact the phase inversion process. Membranes were fabricated with PolarClean and with various additive concentrations and evaporation times. The resulting membranes were characterized using scanning electron microscopy (SEM) and a pycnometer to visualize the pore structure and obtain porosity information. Membrane performance, including water flux and bovine serum albumin rejection, was evaluated using dead-end cell filtration. Membranes fabricated using only PolarClean had fingerlike pore morphology and relatively low protein rejection. The addition of additives resulted in a change in pore architecture and rejection, which is hypothesized to be a result of additives’ volatility, humidity, and destabilization of liquid–liquid separation. This study provides a more detailed understanding of the impact of additives on the resulting ABS membrane structure and performance, with a focus on safer solvents.